PERAN KONFLIK KERJA-KELUARGA DALAM MEMEDIASI KONTRIBUSI DUKUNGAN SOSIAL TERHADAP KEPUASAN KERJA PADA PERAWAT PEREMPUAN - Alparisi Sirajuddin; M. Zein Permana (Departemen Psikologi Universitas Pendidikan Indonesia, 2018)
This study to examine the role of work-family conflict in mediating relationships of social support and job satisfaction in female nurses. The approach used hierarchical regression analysis with social support as independent variable, job satisfaction as dependent variable, and work-family conflict (WFC) as mediator. Each variable was measured using a questionnaire given to participants consisting of 80 female nurses. The study found that social support had a significant positive contribution to nurse job satisfaction, and the contribution was mediated by work-family conflict.